PERAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI SD NEGERI 05 SALIDO KECIL - Rahman, Yulia; Rejeki, Rejeki (STKIP Pesisir Selatan, 2025)
Student motivation in elementary school is crucial because it lays the foundation for success in subsequent levels of education. Children who lack sufficient motivation often face challenges in the learning process, such as lack of active participation in class and a decline in their academic performance. Strong motivation is crucial to help children stay focused and enthusiastic in pursuing their educational goals. This study aims to determine the rolr of parents in increasing student learning motivation. Based on theory, parents have an important rolr in shaping student learning motivasion through emotional suppor, supervision and motivation in the form of attention, guidance, learning facilities at home, and involvementin school activities. This study uses a qualitative researchmethod. The results show that the role of parents in increasing student learning motivation in elementary school includes learning support at home, supervision of schoolwork, and motivation to srchieve academic archievement. This study concludes that the role of parents is very important in increasing student learning motivation in elementary school and helping them achieve academic success. Therefore, parents should be given adequate information and support to be able to play and active role playand active role in increasing their children’s learning motivation.